Importance of biomass energy as alternative to other sources in Turkey - Gokcol, Cihan; Dursun, Bahtiyar; Alboyaci, Bora; Sunan, Erkan (Elsevier Sci Ltd, 2009)
Energy plays a vital role in socio-economic development and raising standards of human beings. Turkey is a rapidly growing country; both its population and economy are expanding each year so its energy demand increases correspondingly and this increasing demand has to be met for keeping sustainable development in the economy and raising living conditions of mankind. Although Turkey has many energy sources, it is a big energy importer. Turkey has a lot of potential to supply its own energy, which could be put to use in order to avoid this energy dependence. Additionally, Turkey is a country that has an abundance of renewable energy sources and can essentially provide all energy requirements from indigenous energy sources. Biomass is one of the most promising energy sources considered to be alternative to conventional ones. This paper investigates the importance of biomass energy in Turkey. Additionally, the potential of biomass and its utilization in Turkey are presented in detail. Turkey has always been one of the major agricultural countries of the world. The importance of agriculture is increasing due to biomass energy being a major resource of Turkey. Like many developing countries, Turkey relies on biomass to satisfy much of its energy requirements. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Biomass energy; Renewable energy; Turkey